Proposal for changing the rules of water polo - Lozovina, M.; Lozovina, V. (Sport Science - International Scientific Journal of Kinesiology, 2019)
Based on the comprehensive scientific analysis of water polo game, after the Extraordinary Congress of International Water Sports Organization (FINA) in Hangzhou, China, in 2018, accepted some of the proposed changes to the rules of water polo game, skeptical for these changes, considering them as a insufficient "cosmetic contribution" which will not contribute to the attractiveness of this game, we are free to suggest, with arguments, changes of the rules of a water polo game convinced that the changes which are suggested are only and the right way to improve water polo game, to become truly attractive to the audience, ceases to be a rough play full of physical contacts in which the raw power is in absolute advantage over the idea and intelligent tactical behavior of the player and what today's water polo is. The proposed changes, if accepted, will substantially change the work of the coaches as well as the very appearance of the game. The players will be brought to the stand by their conceptuality, intelligent technical-tactical solutions and behavior. The proposed changes to the Rules of the game are, with previous arguable explanations, articulated with changes in FINA Water Polo Rules 2019 - 2021 Amendments, Additions, Interpretations and Explanations Valid as of February, 2019.